2004
DOI: 10.2139/ssrn.616611
|View full text |Cite
|
Sign up to set email alerts
|

Non-Parametric Inference for Bivariate Extreme-Value Copulas

Abstract: Consider a continuous random pair (X,Y [Biometrika 84 (1997) 567-577]. In this paper, rank-based versions of these estimators are proposed for the more common case where the margins of X and Y are unknown. Results on the limit behavior of a class of weighted bivariate empirical processes are used to show the consistency and asymptotic normality of these rank-based estimators. Their finite-and large-sample performance is then compared to that of their known-margin analogues, as well as with endpoint-corrected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…In case of known margins, variance-minimizing weight functions λ j can be determined adaptively by ordinary least squares (Segers, 2007;Gudendorf and Segers, 2011). However, if the marginal distributions are unknown, these endpoint cor-rections are asymptotically irrelevant (Genest and Segers, 2009), since…”
Section: Nonparametric Estimation Of the Dependence Functionmentioning
confidence: 99%
“…In case of known margins, variance-minimizing weight functions λ j can be determined adaptively by ordinary least squares (Segers, 2007;Gudendorf and Segers, 2011). However, if the marginal distributions are unknown, these endpoint cor-rections are asymptotically irrelevant (Genest and Segers, 2009), since…”
Section: Nonparametric Estimation Of the Dependence Functionmentioning
confidence: 99%
“…Typically, the convergence above holds in the stronger topology of uniform convergence. The limit process G is a centered Gaussian process, and ε n is equal to the reciprocal of the square root of the effective sample size, i.e., the number of block maxima (Deheuvels 1991;Capéraà, Fougères & Genest 1997;Segers 2007) or the number of high-threshold exceedances (Capéraà & Fougères 2000;Einmahl, de Haan & Piterbarg 2001). By Theorem 1, equation (14) implies that the asymptotic distribution of the projection estimatorÂ…”
Section: Moreover If the Integer Sequence M N Is Such Thatmentioning
confidence: 99%
“…As shown in [82], the weights (1 − t) and t in de Deheuvels estimator (17) can be understood as pragmatic choices that could be replaced by suitable weight functions β 1 (t) and β 2 (t):…”
Section: Nonparametric Estimationmentioning
confidence: 99%
“…Solving the resulting differential equation for A and replacing unknown quantities by their sample versions yields the CFG-estimator. In [82] however, it was shown that the estimator admits the simpler representation…”
Section: Nonparametric Estimationmentioning
confidence: 99%